The Effect of Green Tea Extract on Individual Components of Metabolic Syndrome in Women Who Are Post-menopause. (7th June 2021) - Samavat, Hamed; Philippsborn, Talia; Kurzer, Mindy; Radler, Diane Rigassio
Abstract: Objectives: Green tea intake may have a role in weight management and glucose control. Given the rise in prevalence of metabolic syndrome (MetS) among aging women, research regarding green tea's effect on MetS is warranted. This study aimed to determine whether green tea extract (GTE) supplementation improves components of MetS among women who are post-menopause. Methods: This study was a secondary analysis of the Minnesota Green Tea Trial (MGTT), a double-blinded randomized controlled trial. Participants were a subset of the MGTT who had MetS at baseline. Participants were instructed to take four GTE capsules containing a mean (SD) 843 (44) mg epigallocatechin gallate (EGCG) or placebo daily for 12 months. Waist circumference, HDL-cholesterol, triglyceride, fasting blood glucose, diastolic and systolic blood pressure levels were measured at baseline and month 12, and changes were compared and stratified by catechol-O-methyltransferase enzyme ( COMT ) genotype, BMI, and the number of antihypertensive medications. One-way and two-way ANCOVA tests adjusting for age and BMI at baseline were also used for comparisons of the endpoints between treatment groups and for exploratory analyses. Results: The GTE group ( n  = 49) experienced a significant reduction in HDL-cholesterol concentrations compared to an increase in the placebo group ( n  = 63) (GTE: −0.45 ± 1.27 mg/dL, Placebo: 2.95 ± 0.77 mg/dL, P  = 0.04). Those in the GTE group with high-activity COMT genotype had a significant reduction in SBP compared to placebo. (Low/intermediate-activity COMT genotype GTE: −0.79 ± 2.08 mmHg, Placebo: −3.26 ± 1.67 mmHg; High-activity COMT genotype GTE: −5.64 ± 2.73 mmHg, Placebo: 1.58 ± 3.00 mmHg, P -interaction = 0.048). Those in the GTE group who took three antihypertensive medications had a significant reduction in waist circumference compared to placebo (GTE: −7.91 ± 3.72cm,  placebo: 3.50 ± 2.64 cm, P -interaction = 0.04). No significant changes were found for the other endpoints. Conclusions: GTE supplementation for 12 months was not associated with improvements in individual components of MetS in this population. GTE supplementation may help reduce SBP among women with high-activity COMT genotype and waist circumference in those who take three antihypertensive medications. Funding Sources: NIH/National Cancer Institute.